Humour, asymmetric polarisation and hatred in contemporary Brazil: brief notes - Paul Gruda, Mateus Pranzetti [UNESP] (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2021)
Taking the asymmetric polarisation of Brazilian contemporary context, we tried to reflect regarding aspects related to hate pointed to others, which unlike of being understood as adversaries are elevated to the condition of enemies who must be eliminated. In a general way, hatred is widespread and connected in and by verbal violence discourse, and because of that, we focused on the topic of language. We consider language as something important, since it constitutes reality, relations and the way we subjectify. We choose humour discourse as study object in our reflection because of the comprehension that attacks uttered within this social-historical-cultural context are using a humoristic mode of operating, which apparently could turn those offensive things into softly ones, besides of justifying them. In our text, we also present a perspective that indicates a wide opening and complexification process on understanding what is humoristic and what is not humoristic.
Keywords: Polarisation; hatred; humour